2010
DOI: 10.1095/biolreprod.109.083121
|View full text |Cite
|
Sign up to set email alerts
|

The Severity of Chorioamnionitis in Pregnant Sheep Is Associated with In Vivo Variation of the Surface-Exposed Multiple-Banded Antigen/Gene of Ureaplasma parvum1

Abstract: Ureaplasma species are the bacteria most frequently isolated from human amniotic fluid in asymptomatic pregnancies and placental infections. Ureaplasma parvum serovars 3 and 6 are the most prevalent serovars isolated from men and women. We hypothesized that the effects on the fetus and chorioamnion of chronic ureaplasma infection in amniotic fluid are dependent on the serovar, dose, and variation of the ureaplasma multiple-banded antigen (MBA) and mba gene. We injected high- or low-dose U. parvum serovar 3, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
72
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(83 citation statements)
references
References 54 publications
(72 reference statements)
7
72
3
1
Order By: Relevance
“…These data demonstrate that Ureaplasma can chronically colonize the amniotic fluid for at least 85 days and suggest that amniotic fluid, a rich source of urea, can support the long-term growth of these microorganisms. We further demonstrated that U. parvum was consistently isolated from the chorioamnion and fetal lung following chronic intra-amniotic infection (205,215,(218)(219)(220) and was also isolated from the umbilical cord and other fetal tissues, including cerebrospinal fluid, gut, kidney, liver, and spleen (205). These findings are consistent with human studies that have reported that Ureaplasma spp.…”
Section: Animal Models Have Helped To Elucidate the Pathogenesis Of Usupporting
confidence: 90%
See 4 more Smart Citations
“…These data demonstrate that Ureaplasma can chronically colonize the amniotic fluid for at least 85 days and suggest that amniotic fluid, a rich source of urea, can support the long-term growth of these microorganisms. We further demonstrated that U. parvum was consistently isolated from the chorioamnion and fetal lung following chronic intra-amniotic infection (205,215,(218)(219)(220) and was also isolated from the umbilical cord and other fetal tissues, including cerebrospinal fluid, gut, kidney, liver, and spleen (205). These findings are consistent with human studies that have reported that Ureaplasma spp.…”
Section: Animal Models Have Helped To Elucidate the Pathogenesis Of Usupporting
confidence: 90%
“…However, these findings are not always consistent, with a recent study by our group demonstrating no correlation between the numbers of Ureaplasma present within placentae, the species/serovar present, or the ethnicity of women infected with Ureaplasma and the incidence or severity of histological chorioamnionitis (62). Furthermore, animal model studies in which Ureaplasma infections have been established with the same strain and dose of U. parvum resulted in divergent inflammatory responses within the chorioamnion (59,205,206) and within other genital tract tissues (207), suggesting that the development or magnitude of host immune responses may contribute to the severity of chorioamnionitis. Indeed, we have demonstrated that the human Ureaplasma spp.…”
Section: Ureaplasma Spp As Etiological Agents Of Chorioamnionitismentioning
confidence: 82%
See 3 more Smart Citations